Effects of Interactive Media on Critical and Creative Thinking - Mochamad Ridwan; Rahmawati Al Adha Nikmah (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2022)
Physical Education Teacher Education (PETE) need to support the student's critical and creative mindset building in various ways and strategies. One of them is by using interactive learning media. Interactive media can provide a stimulus for student development. Interactive media can facilitate the teaching and learning process because it allows students to actively think critically and creatively in performing motor tasks so that they do not get bored during the learning process in the field. The research method used was a quantitative method using a pre-experimental and one-group pretest-posttest design. Samples of this study were selected using simple random sampling. The data obtained were analyzed using Paired Sample T-test. The student critical thinking skill data show the sig value or p-value of (0.000). The student creative thinking skill data show the sig or p-value of (0.000) with a significant level of 0.05. It indicates a considerable influence on the use of interactive media. Therefore, it could be a solution to overcome problems by improving critical and creative thinking skills. In general, the use of interactive media can be developed according to the needs of the material provided by PETE to their students.